Molecular Identification of Lactic Acid Bacteria Approach to Sustainable food Security - Dessy Abdullah; Sandeep Poddar; Ramesh Prasath Rai; Endang Purwati; Nadia Purnama Dewi; Yudha Endra Pratama (SAGE Publishing, 2021)
Background: Dadiah is a traditional dish from West Sumatra made from buffalo milk, which is fermented in bamboo tubes and left at room temperature for ±2 days. Dadiah is included in the staple food category because it contains Lactic Acid Bacteria (LAB) which has the potential to be a probiotic. This study aims to determine the identification and characterization of LAB from Dadiah from Halaban, Kab. Fifty Cities, West Sumatra. Design and Methods: A survey method was used in this research with a descriptive analysis, Antimicrobial activity testing was done with bacteria Escherichia coli O157, Staphylococcus aureus, Listeria monocytogenes, and Listeria innocua. Molecular identification was done using the 16S rRNA gene. Results: Probiotic candidate test with the best results in testing for resistance to stomach acid at pH3 with the viability of 65.98%, bile salt resistance 0.3%, viability of 54.90% from 2DA isolates. Antimicrobial activity with the best clear zone area results was obtained in 2DA isolates with Escherichia coli O157 test bacteria of 21.16 mm, Staphylococcus aureus with a clear zone area of 23.17 mm, Listeria innocua of 19.24 mm and Listeria monocytogenes with a clear zone area 18.23 mm in 4DA isolate, LAB identification using 16S sRNA gene, results of running PCR base length 1419bp. Conclusions: Phylogenetic analysis shows that Dadiah of Limapuluh Kota Regency is a kin to Lactobacillus plantarum. The superiority of identification technology by using 16S rRNA gene only can be conducted if the nucleotide sequence information of the targeted bacteria is known beforehand.